2009
DOI: 10.1038/bmt.2008.424
|View full text |Cite|
|
Sign up to set email alerts
|

Allogeneic hematopoietic SCT for patients with autoimmune diseases

Abstract: Allogeneic hematopoietic SCT (HSCT) has been used as treatment for single patients with autoimmune diseases (AD). To summarise currently available information, we analyzed all patients who underwent allogeneic HSCT for AD and who reported to the European Group for Blood and Marrow Transplantation (EBMT) database. Thirty-five patients receiving 38 allogeneic transplantations for various hematological and non-hematological AD were identified. Four patients had had an allogeneic HSCT for a conventional hematologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 19 publications
4
53
0
Order By: Relevance
“…Treatment-related mortality at 2 years follow-up was 22.1% (95% confidence interval: 7.3 --36.9%). 6 We report the case of a 7-year-old boy with ES and concomitant HAE, both cured by allogeneic cord blood SCT. Only one similar case was published in 2005 correcting myelofibrosis and recurrent acquired angioedema following nonmyeloablative allo-SCT.…”
mentioning
confidence: 99%
“…Treatment-related mortality at 2 years follow-up was 22.1% (95% confidence interval: 7.3 --36.9%). 6 We report the case of a 7-year-old boy with ES and concomitant HAE, both cured by allogeneic cord blood SCT. Only one similar case was published in 2005 correcting myelofibrosis and recurrent acquired angioedema following nonmyeloablative allo-SCT.…”
mentioning
confidence: 99%
“…1,2 Kidney or lung involvement at diagnosis is associated with a threefold increased mortality, and up to 30% of patients with WG requiring intensive care die within the first month. 3,6 Immunoablative chemotherapy with subsequent auto-SCT has become an accepted therapy for severe autoimmune diseases, 7 but disease recurrence remains a major obstacle. 4 Auto-SCT for WG has been associated with persistence of ANCAs and new autoimmune phenomena.…”
mentioning
confidence: 99%
“…Some studies have demonstrated that cord blood stem cells have the potential to induce vasculogenesis. 11 There have been reports of CBT for AID, such as Evans syndrome, especially in pediatric settings, 3,8 but only anecdotal data are available. To our knowledge, this is the first report indicating the effectiveness of CBT for TA.…”
Section: Pre-cbtmentioning
confidence: 99%
“…1-3, 8 Daikeler et al 8 performed a retrospective analysis of 35 patients receiving allogeneic HSCT for AID, and its response rate and TRM at 2 years were 79% (CR 55% and PR 24%) and 22.1%, respectively. They concluded that allogeneic HSCT can induce remission in patients with refractory AID.…”
mentioning
confidence: 99%